Bacterial synthesized silver nanoparticle inhibits Rhizoctonia solani Kuhn, the causal organism for sheath blight disease of rice - Behera, Lopamudra; Chandra, Ram; Lenka, Srikanta; Mahanty, Arabinda; Kumar, Sumit; Rath, Prakash Chandra (ORYZA-An International Journal of Rice, 2023)
Rhizoctonia solani Kuhn (AG 1-IA) is one of the most devastating pathogens of rice causing sheath blight disease and being a prime reason for the unsatisfactory productivity of rice in India. The goal of the present study was to investigate the efficacy of silver nanoparticles (AgNPs) synthesized using an agriculturally important bacterium, Pseudomonas fluorescens OKC, in managing the sheath blight disease of rice. Successful biosynthesis of AgNPs was monitored by UV-visible spectroscopy, showing a peak at 432 nm. The AgNPs were further characterized using a Transmission Electron Microscope (TEM), Dynamic Light Scattering (DLS) and Fourier Transform Infrared spectroscopy (FT-IR). The TEM result confirmed that the size of the synthesized nanoparticles was less than 100nm. DLS results revealed that the average particle size of the AgNPs was 74 nm and the zeta potential was -23.6 mV, indicating that the synthesized nanoparticles were of good stability at room temperature. The antifungal potential of AgNPs was tested against the test fungus in vitro and maximum growth inhibition was recorded in AgNPs treatment (69.09%) as compared to the control. Moreover, this result was further authenticated under net house conditions, where AgNPs successfully reduced the incidence of R.solani Kuhn. The findings showed that the biosynthesized AgNPs inhibited the growth of R. solani Kuhn and could be useful in the management of sheath blight disease in rice.